2021
DOI: 10.1038/s41467-021-21748-6
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation in the lung contributes to virulence and drug tolerance of Mycobacterium tuberculosis

Abstract: Tuberculosis is a chronic disease that displays several features commonly associated with biofilm-associated infections: immune system evasion, antibiotic treatment failures, and recurrence of infection. However, although Mycobacterium tuberculosis (Mtb) can form cellulose-containing biofilms in vitro, it remains unclear whether biofilms are formed during infection in vivo. Here, we demonstrate the formation of Mtb biofilms in animal models of infection and in patients, and that biofilm formation can contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(168 citation statements)
references
References 62 publications
4
141
0
Order By: Relevance
“…CelA1 expression was recently linked with biofilm formation, antibiotic tolerance, and virulence in Mtb ( 9 ). Therefore, Mmr cells in planktonic and biofilm forms with/without CelA1 overexpression were also exposed to rifampicin to determine the MIC and minimum bactericidal concentration (MBC) for this bactericidal first-line TB drug.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CelA1 expression was recently linked with biofilm formation, antibiotic tolerance, and virulence in Mtb ( 9 ). Therefore, Mmr cells in planktonic and biofilm forms with/without CelA1 overexpression were also exposed to rifampicin to determine the MIC and minimum bactericidal concentration (MBC) for this bactericidal first-line TB drug.…”
Section: Resultsmentioning
confidence: 99%
“…The present study shows that Mmr grows in two different biofilm subtypes and that reduced CelA1 hydrolase activity is one of the main triggers of biofilm growth and increased tolerance to rifampicin in both biofilm subtypes. Studies on Mtb and M. smegmatis have demonstrated that cellulose filaments are vital structural constituents of mycobacterial biofilm ECMs as well as essential for biofilm formation and the development of tolerance/persistence ( 9 , 11 , 18 , 19 ). We also show that the Mmr biofilm subtypes show distinct morphologies, with SBFs containing lichen-like structures and PBFs consisting of ribbon-like cords under the same in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes essential for mycobacterial growth ( Sabine et al, 2015 ; Zuniga et al, 2015 ), enzymes associated with fatty acid synthesis ( Tiago et al, 2019 ), and DNA replication have been targeted for new treatment options ( Aggarwal et al, 2017 ; Pradhan and Sinha, 2018 ). However, clinical investigations revealed that the main mechanisms of drug resistance in Mtb are gene mutations and biofilm formation ( Poushali et al, 2021 ; Saba et al, 2021 ). Therefore, screening of natural products and their derivatives ( Guzman et al, 2012 ), new small molecule inhibitors ( Mishra et al, 2018 ), and FDA-approved drugs offers a new approach for the development of novel anti-TB drugs ( Igarashi, 2017 ; Luo et al, 2017 ; Igarashi et al, 2018 ; Nadav et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The complex mycobacterial cell wall, involving capsule and outer/inner membranes connected by a dense mycolyl-arabinogalactanpeptidoglycan with high lipid levels, is the main barrier that protects the bacterial cells against drugs (6). While the mechanisms leading to drug tolerance in TB have remained poorly understood, biofilm formation was recently indicated as one of the strategies to increase viability, tolerance and persistence (7)(8)(9)(10).…”
Section: Introduction (5735 Words)mentioning
confidence: 99%